(untitled) (Philologia, 2021)
The paper deals with an analysis of adaptation methods of generic names of electronic devices from English in the following ten languages: German, Dutch, French, Spanish, Italian, Russian, Polish, Czech, Hungarian and Serbian. The corpus consists of names of twenty-three home entertainment devices, collected from the local websites of several leading world manufacturers. The aim of the comparative analysis has been to establish the following: (1) a typology of methods used in the above languages when adapting English models, and (2) the degree of receptivity of each of these languages to the inﬂuences of English when forming their own vocabulary in this ﬁeld.